An Experimental Investigation on the Effect of Curing Method and Aggregate Type on the Concrete - Ali, Shahrukh; Tiwari, Abhishek (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
The concrete binds our every new construction and from its discovery concrete changes theworld construction system and speed up to the mark, and so to test the important property likecompressive strength of concrete has become so important. And this property of concrete depends onseveral values and among them some very prescribed are, curing method, water quality and type ofaggregate. This study can be done in many ways, with many parameters, but according to further clearobjectives are to examine the concrete and studying its effect on compressive and workability ofconcrete taking as ideal concrete mixed with potable tap water of local area, to justify the compatibilityof Accelerated curing method for determining the compressive strength of concrete on above thetraditional ( water immersing method ) curing methods, to compare the effect of using crushedquartzite as a coarse aggregate in concrete by partially and fully replacement of black metals ( gravel ),to make the comparative study with these three parameters water quality, curing method andreplacement of gravel with crushed quartzite partially and fully. The various tests of compressivestrength determination are performed to take the study to the further level